1984
DOI: 10.1038/ki.1984.178
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of hepatitis B e antigen in membranous glomerulonephritis: Identification by F(ab′)2 fragments of monoclonal antibody

Abstract: The pathogenic ability of hepatitis B e antigen (HBeAg) to induce membranous glomerulonephritis was evaluated by the most specific method presently available. Monoclonal antibody was raised against HBeAg, and F(ab')2 fragments were obtained and labeled with fluorescence. By this reagent, 10 out of 16 patients with membranous glomerulonephritis with hepatitis B surface antigen in the serum revealed granular deposition of HBeAg along glomerular capillary walls. Among the cases with glomerular HBeAg deposits, nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 18 publications
2
34
0
1
Order By: Relevance
“…In HBVMN glomerular deposition of HBsAg [53, 38], HBcAg [37, 40]and HBeAg [67, 68]have been observed. Lai et al [51]used F(ab′) 2 fragments to confirm that HBeAg is the specific component deposited in HBV-associated MN.…”
Section: Pathogenesis Of Hbv-associated Nephropathymentioning
confidence: 99%
See 2 more Smart Citations
“…In HBVMN glomerular deposition of HBsAg [53, 38], HBcAg [37, 40]and HBeAg [67, 68]have been observed. Lai et al [51]used F(ab′) 2 fragments to confirm that HBeAg is the specific component deposited in HBV-associated MN.…”
Section: Pathogenesis Of Hbv-associated Nephropathymentioning
confidence: 99%
“…The other common clinical presentation in children is the nephrotic syndrome. There is a strong male predominance [38, 52, 67, 68]. In adults, proteinuria and the nephrotic syndrome are most common manifestations.…”
Section: Clinical Presentation Of Hbvmnmentioning
confidence: 99%
See 1 more Smart Citation
“…3]. Re cently, hepatitis Be antigen (HBeAg) has been found in glomerular immune deposits in membranous glomerulo nephritis of children, and the pathogenetic role of HBeAg in membranous glomerulonephritis has been em phasized [4][5][6]. It remains uncertain, however, whether HBsAg or HBeAg plays a pathogenetic role in the devel opment of membranoproliferative glomerulonephritis (MPGN) associated with HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…HBe antigen is known to combine with IgG, irrespective of antibody specificity [8]. On the other hand, it has been reported that HBe antigen is present in glomerular deposits of MGN, as demonstrated by fluoresceinated F(ab')2 fragments of monoclonal antibody raised against HBe antigen [9]. Therefore, the question as to whether the IgG de tected by immunofluorescent staining in the glomeruli of HBV-associated MGN is a specific anti-HBe antibody was not answered.…”
Section: Introductionmentioning
confidence: 99%